Studi Kasus UMKM Usaha Martabak Manis Bang Aldo - Teguh H.S; Naufal G.R; Nani Hartati (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
This research aims to analyze marketing strategies and factors that influence the success of SMEs in the martabak business in the Sukatani area, Bekasi Regency, which coincides in Sukadarma Village, Kampung Serengseng Jaya. MSMEs play an important role in the local economy, but often face challenges in competing with larger businesses. To identify effective strategies, we conducted a qualitative study using in-depth interviews with Martabak MSME owners and used SWOT analysis to identify strengths, weaknesses, opportunities and threats faced. The research results show that the use of social media as a marketing tool, product innovation and service quality are the main factors that contribute to the success of martabak MSMEs. Additionally, partnerships with local suppliers and a deep understanding of consumer preferences have also proven important. The challenges faced include intense competition, fluctuations in raw material prices, and limited capital. Thus, this research provides insight into the best practices that can be implemented by martabak MSMEs to increase the competitiveness and sustainability of their businesses. The proposed strategic recommendations include increasing digital skills, product diversification, and developing customer loyalty programs